Preparation method of novel environment-friendly water-resistant adhesive for thermo-sensitive paper label
Through the composite technology of polyurethane grafted tannins with soy protein and esterified starch-modified epoxy resin, the environmental protection and compatibility problems of epoxy resin adhesives are solved, and high viscosity, waterproof and environmentally friendly adhesives are achieved. Effect of agent.
Patent Information
- Application Number
- CN202411450312.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-01-17
AI Technical Summary
The existing epoxy resin adhesives have environmental problems, and the tannins are poor in compatibility and interface separation when blended with biopolyester, which affects the adhesive strength and waterproofing effect of the adhesive.
Polyurethane grafted tannins are mixed with soy protein, combined with esterified starch modified epoxy resin, improve hydrophobicity and viscosity through physical means such as microwave and ultrasound, and form polyurethane elastic fibers and epoxy resin to compound, increasing compatibility and machinery performance.
It realizes the effect of environmentally friendly, high viscosity and waterproof adhesive, improves the water resistance and adhesion of the adhesive, and reduces the viscosity to meet environmental protection and functional requirements.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of adhesive preparation, in particular to a method for preparing a novel environmentally friendly water-resistant adhesive for thermal paper labels. Background Art
[0002] Adhesives include organic adhesives and inorganic adhesives. Organic adhesives mainly include silicone resin, silicone rubber, polyimide, phenolic resin, epoxy resin, etc., while inorganic adhesives mainly include silicates, alkali metal phosphates and silica sol, etc. There are many types of organic adhesives, and the bonding strength to materials is generally high. For example, epoxy adhesives are called all-purpose adhesives. However, epoxy resin adhesives currently on the market have various other organic chemicals added, which do not meet the requirements of green environmental protection. In addition, excessive exposure to such organic chemicals is likely to have adverse effects on the human body.
[0003] When developing a new environmentally friendly adhesive, it can be considered to add tannins to polyesters to improve their biological activity. However, directly blending tannins with materials such as bio-polyesters will lead to problems such as poor compatibility and interface separation. How to effectively and evenly disperse tannins in adhesives is also a major technical difficulty. In addition, the addition of a large proportion of protein, starch, etc. also causes a certain decrease in the adhesive strength, affecting the waterproof effect during use. How to overcome the above problems is the research direction of this invention. Therefore, a new environmentally friendly water-resistant adhesive for thermal paper labels is introduced to meet the expected market demand. Summary of the invention
[0004] The object of the present invention is to provide a method for preparing a novel environmentally friendly water-resistant adhesive for thermal paper labels to solve the problems existing in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solution: a method for preparing a new environmentally friendly water-resistant adhesive for thermal paper labels, comprising the following preparation steps: (1) Weigh 1 part of tannic acid and 0.1-0.5 parts of stannous octoate, mix at 90-160°C, stir at 200 r / min for 20 min, cool naturally to 25°C, add 1-5 parts of 1,4-butenediol, stir magnetically at 500-600 r / min for 2 h, filter and collect the precipitate, air dry naturally, and dry at -0.096 MPa vacuum degree and 30-40°C for 12-48 h to obtain 1,4-butenediol containing tannic acid; (2) 1.2-2 parts of diphenylmethane diisocyanate and 1 part of 1,4-butenediol are mixed, reacted at 90°C for 90 minutes, cooled to 40°C, 1.8-2 parts of 1,4-butenediol containing tannin are added, reacted at 80°C for 16 hours, cooled to 5°C again, and then 4 parts of dimethylacetamide are slowly added under vigorous stirring to prepare a polyurethane solution; 0.012 times the weight of the polyurethane solution of 4,4'-butylenebis(3-methyl-6-tert-butylphenol) and 0.01 times the weight of the polyurethane solution of 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole are added to the polyurethane solution, stirred at 60r / min for 20 minutes, and degassed under reduced pressure at room temperature to produce a spinning solution; (3) dissolving 2 parts of soybean protein in 6-8 parts of sodium hydroxide aqueous solution at a temperature of 40-60° C., reacting under a microwave of 600-900 MHz for 2 h to obtain a soybean protein pre-liquid, and then adding an initiator in an amount of 0.01-0.1 times the weight of the soybean protein pre-liquid to prepare a soybean protein solution; mixing 1 part of the soybean protein solution with 3-5 parts of spinning stock solution, stirring at a speed of 200 r / min for 6 h to prepare a spinning solution, and dry spinning the spinning solution at a spinning speed of 800 m / min and a hot air temperature of 200° C. to prepare a soybean protein polyurethane elastic fiber; (4) Disperse 2 parts of corn starch in 2-3 parts of ethyl acetate under ultrasonic conditions, add 0.2 parts of pyridine dropwise, continue ultrasonication for 0.5 h, add 0.1-0.3 parts of aminoacetyl chloride dropwise and stir at 200 r / min for 1 h, react at 25°C for 0.5 h, add 10 parts of ethanol to terminate the reaction, let stand for 2 h, wash repeatedly with ethanol by centrifugation 4-5 times, and dry the solid product after centrifugation in a forced air oven at 80°C for 24 h to obtain esterified starch; mix 10 parts of esterified starch and 10 parts of poly(vinyl alcohol) Ethylene glycol-400 and 1 part of sulfuric acid solution were stirred at 150°C and 100 r / min for 12 hours to obtain an esterified starch modifier; 10 parts of epoxy resin E-51 were mixed with 1-2 parts of esterified starch modifier, stirred at 100 r / min for 1 hour, placed in an oven at 180°C for 12 hours, taken out, cooled to 25°C, 1 part of anhydrous ethanol and 1 part of diethylenetriamine were added, stirred at 100 r / min for 1 hour, and vacuumed at 0-10°C to obtain a modified epoxy resin; (5) Heat 15-45 parts of deionized water to 80°C, slowly add 15-45 parts of polyvinyl alcohol at a stirring speed of 60 r / min and heat to 90-95°C. After complete dissolution, cool to 75-85°C, add 10-20 parts of butanol and 6-8 parts of boric acid, stir at 60 r / min for 30 min, then add 12-24 parts of soybean protein polyurethane elastic fiber, 2-4 parts of urea, and 13-26 parts of modified epoxy resin, stir at 60 r / min and heat to 90-95°C. After reacting for 60 min, lower the temperature to 60-75°C, add 8 parts of sodium lauryl sulfate, stir at 60 r / min for 15-20 min, cool and discharge the material to obtain a new environmentally friendly water-resistant adhesive for thermal paper labels.
[0006] Furthermore, the natural air drying time in step (1) is 12-36 hours.
[0007] Furthermore, the speed of the vigorous stirring in step (2) is 1000-2000 r / min.
[0008] Furthermore, the mass fraction of the sodium hydroxide aqueous solution in step (3) is 1-5%.
[0009] Furthermore, in step (3), the initiator is hydrogen peroxide.
[0010] Furthermore, the diameter of the fiber produced in step (3) is 200-1500 nm.
[0011] Furthermore, the sulfuric acid solution in step (4) is a 1 mol / L sulfuric acid aqueous solution.
[0012] Furthermore, the ultrasonic condition in step (4) is: power is 60-80kHz.
[0013] Furthermore, in step (4), the pressure is evacuated to 0.096 MPa.
[0014] Furthermore, in step (5), the discharge temperature is 40-50°C.
[0015] Compared with the prior art, the beneficial effects achieved by the present invention are: The invention prepares an adhesive by mixing polyurethane grafted tannin with soybean protein and adding epoxy resin modified by esterified starch as raw materials, so as to achieve environmental protection, high viscosity and waterproof effects.
[0016] Firstly, diphenylmethane diisocyanate and 1,4-butenediol are mixed and reacted to generate a polyurethane prepolymer with isocyanate as the terminal, and then grafted and copolymerized with tannic acid to generate a spinning solution to prepare micron-sized polyurethane elastic fibers; then, it is introduced into soybean protein to obtain soybean protein polyurethane elastic fibers, and the double bonds in the fiber molecular chain are polymerized with the amino free radicals of soybean protein, and multiple phenolic hydroxyl groups are introduced into the molecular structure of soybean protein to improve the hydrophobicity of soybean protein, thereby improving the water resistance of the adhesive, and synergistically with the radiation physical means of microwaves to change the aggregation mode between protein molecules to achieve a better hydrophobic effect. In addition, the surface of the polyurethane elastic fiber grafted with tannic acid contains a large number of phenolic hydroxyl groups, which can act as a hydrogen donor and combine with free radicals to terminate the chain reaction caused by free radicals, thereby achieving the purpose of anti-oxidation and improving viscosity. At the same time, tannic acid can reduce the colloidal interaction between proteins, further destroy the secondary structure of the protein, and form a new dense network structure with the protein to prevent the invasion of water molecules, taking into account the effects of reducing the viscosity of the adhesive and waterproofing.
[0017] Secondly, the present invention uses aminoacetyl chloride as a reagent to esterify starch, and uses the starch as a filler additive. The amino groups on the surface of the starch are cross-linked with the polar groups of the epoxy resin, thereby increasing the compatibility of the starch with the epoxy resin, making the starch evenly dispersed in the epoxy resin, and showing an obvious steric hindrance effect. Then, the soybean protein polyurethane elastic fiber is added to the epoxy resin, and the starch adheres to the fiber surface to form a chain structure and is composited with the resin, thereby improving the mechanical bonding performance of the adhesive. As an environmentally friendly adhesive for notes, the adhesive uses biological protein, starch, and epoxy resin as raw materials, so that the adhesive can be biodegraded and is effectively environmentally friendly. The polyurethane elastic fiber in the adhesive can also generate hydrogen bonding force with the plant fiber on the paper. Under the synergistic effect of the protein, the adhesion of the adhesive for thermal paper labels is further improved. DETAILED DESCRIPTION
[0018] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0019] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the new environmentally friendly water-resistant adhesive for thermal paper labels prepared in the following examples are as follows: Adhesion: The adhesives prepared in the examples and comparative examples were used as substrates with thermal paper to prepare 100 mm×20 mm×3 mm environmentally friendly water-resistant tapes. The adhesion of the biodegradable tape was tested according to the standard GB / T4851, and the average value was calculated after 5 measurements.
[0020] Peel strength: The adhesives prepared in the examples and comparative examples were used as substrates with thermal paper to prepare 100 mm×20 mm×3 mm environmentally friendly water-resistant tapes. The peel strength of the biodegradable tape was tested according to standard GB / T2792, and the average value was calculated after 5 measurements.
[0021] Biodegradability: 10 g of the adhesives prepared in the examples and comparative examples were placed in the soil in a natural environment for composting degradation. The temperature was maintained at 25° C. and the humidity was maintained at 50%. After six months, the residual amount was observed and the degradation rate was calculated.
[0022] Water resistance: The adhesives of the embodiments and comparative examples were evenly applied on thermal paper of a size of 100 mm × 20 mm × 3 mm, then balanced at 25°C for 24 hours, and then placed in a water bath at 65°C, covered with a lid and immersed. The test piece was taken out after 4 hours, and the peel strength of the adhesive tape was tested according to standard GB / T2792, and the average value was calculated after 5 measurements.
[0023] Example 1; (1) Weigh 1 part of tannic acid and 0.1 part of stannous octoate, mix at 90°C, stir at 200 r / min for 20 min, cool naturally to 25°C, add 1 part of 1,4-butenediol, stir magnetically at 500 r / min for 2 h, filter the precipitate, air-dry for 12 h, and dry at -0.096 MPa and 30°C for 12 h to obtain 1,4-butenediol containing tannic acid; (2) 1.2 parts of diphenylmethane diisocyanate and 1 part of 1,4-butenediol were mixed, reacted at 90°C for 90 minutes, cooled to 40°C, 1.8 parts of 1,4-butenediol containing tannin was added, reacted at 80°C for 16 hours, cooled to 5°C again, and then 4 parts of dimethylacetamide were slowly added under stirring at 1000 r / min to prepare a polyurethane solution; 0.012 times the weight of the polyurethane solution of 4,4'-butylenebis(3-methyl-6-tert-butylphenol) and 0.01 times the weight of the polyurethane solution of 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole were added to the polyurethane solution, stirred at 60 r / min for 20 minutes, and degassed under reduced pressure at room temperature to produce a spinning solution; (3) Dissolve 2 parts of soybean protein in 6 parts of 1% sodium hydroxide aqueous solution at 40°C, react under a 600 MHz microwave for 2 h to obtain a soybean protein pre-liquid, then add 0.01 times the weight of the soybean protein pre-liquid as an initiator, hydrogen peroxide, to prepare a soybean protein solution; mix 1 part of the soybean protein solution with 3 parts of spinning stock solution, stir at a speed of 200 r / min for 6 h to prepare a spinning solution, and dry-spin the spinning solution at a spinning speed of 800 m / min and a hot air temperature of 200°C to prepare a soybean protein polyurethane elastic fiber with a diameter of 200 nm; (4) Disperse 2 parts of corn starch in 2 parts of ethyl acetate under 60 kHz ultrasound, add 0.2 parts of pyridine dropwise, continue ultrasound for 0.5 h, add 0.1 parts of aminoacetyl chloride dropwise and stir at 200 r / min for 1 h, react at 25 °C for 0.5 h, add 10 parts of ethanol to terminate the reaction, let stand for 2 h, wash with ethanol by centrifugation 4 times, dry the solid product after centrifugation in a forced air oven at 80 °C for 24 h to obtain esterified starch; mix 10 parts of esterified starch, 10 parts of polyethylene glycol-400, and 1 part of 1 mol / L sulfuric acid aqueous solution was stirred at 150°C and 100r / min for 12h to obtain an esterified starch modifier; 10 parts of epoxy resin E-51 were mixed with 1 part of esterified starch modifier, stirred at 100r / min for 1h, placed in an oven at 180°C for 12h, taken out, cooled to 25°C, 1 part of anhydrous ethanol and 1 part of diethylenetriamine were added, stirred at 100r / min for 1h, and vacuumed to 0.096MPa at 0°C to obtain a modified epoxy resin; (5) Heat 15 parts of deionized water to 80°C, slowly add 15 parts of polyvinyl alcohol at a stirring speed of 60 r / min and heat to 90°C. After complete dissolution, cool to 75°C, add 10 parts of butanol and 6 parts of boric acid, stir at 60 r / min for 30 min, then add 12 parts of soybean protein polyurethane elastic fiber, 2 parts of urea, and 13 parts of modified epoxy resin, stir at 60 r / min and heat to 90°C. After reacting for 60 min, lower the temperature to 60°C, add 8 parts of sodium lauryl sulfate, stir at 60 r / min for 15 min, cool to 40°C and discharge to obtain a new environmentally friendly water-resistant adhesive for thermal paper labels.
[0024] Example 2; (1) Weigh 1 part of tannic acid and 0.3 parts of stannous octoate, mix at 125°C, stir at 200 r / min for 20 min, cool naturally to 25°C, add 3 parts of 1,4-butenediol, stir at 550 r / min for 2 h, filter the precipitate, air dry naturally for 24 h, and dry at -0.096 MPa and 30°C for 30 h to obtain 1,4-butenediol containing tannic acid; (2) 1.6 parts of diphenylmethane diisocyanate and 1 part of 1,4-butenediol were mixed in a molar ratio of 1.6, reacted at 90°C for 90 minutes, cooled to 40°C, added with 1.9 parts of 1,4-butenediol containing tannin, reacted at 80°C for 16 hours, cooled to 5°C again, and then slowly added with 4 parts of dimethylacetamide under stirring at 1500 r / min to prepare a polyurethane solution; 0.012 times the weight of the polyurethane solution of 4,4'-butylenebis(3-methyl-6-tert-butylphenol) and 0.01 times the weight of the polyurethane solution of 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole were added to the polyurethane solution, stirred at 60 r / min for 20 minutes, and degassed under reduced pressure at room temperature to produce a spinning solution; (3) Dissolve 2 parts of soybean protein in 7 parts of 3% sodium hydroxide aqueous solution at 50°C, react under a microwave of 750 MHz for 2 h to obtain a soybean protein pre-liquid, then add 0.05 times the weight of the soybean protein pre-liquid as an initiator, hydrogen peroxide, to prepare a soybean protein solution; mix 1 part of the soybean protein solution with 3 parts of spinning stock solution, stir at a speed of 200 r / min for 6 h to prepare a spinning solution, and dry-spin the spinning solution at a spinning speed of 800 m / min and a hot air temperature of 200°C to prepare a soybean protein polyurethane elastic fiber with a diameter of 850 nm; (4) 2 parts of corn starch were dispersed in 2.5 parts of ethyl acetate under 70 kHz ultrasound, 0.2 parts of pyridine were added dropwise, ultrasound was continued for 0.5 h, 0.2 parts of aminoacetyl chloride were added dropwise and stirred at 200 r / min for 1 h, reacted at 25 °C for 0.5 h, 10 parts of ethanol were added to terminate the reaction, and the mixture was allowed to stand for 2 h. The ethanol was repeatedly centrifuged and washed 5 times. The solid product after centrifugation was placed in a forced air oven at 80 °C and dried for 24 h to obtain esterified starch. 10 parts of esterified starch, 10 parts of polyethylene glycol-400, and 1 part of 1 mol / L sulfuric acid aqueous solution was stirred at 150°C and 100r / min for 12h to obtain an esterified starch modifier; 10 parts of epoxy resin E-51 were mixed with 1.5 parts of esterified starch modifier, stirred at 100r / min for 1h, placed in an oven at 180°C for 12h, taken out, cooled to 25°C, 1 part of anhydrous ethanol and 1 part of diethylenetriamine were added, stirred at 100r / min for 1h, and vacuumed to 0.096MPa at 5°C to obtain a modified epoxy resin; (5) Heat 30 parts of deionized water to 80°C, slowly add 30 parts of polyvinyl alcohol at a stirring speed of 60 r / min and heat to 93°C. After complete dissolution, cool to 80°C, add 15 parts of butanol and 7 parts of boric acid, stir at 60 r / min for 30 min, then add 18 parts of soybean protein polyurethane elastic fiber, 3 parts of urea, and 20 parts of modified epoxy resin, stir at 60 r / min and heat to 93°C. After reacting for 60 min, lower the temperature to 67°C, add 8 parts of sodium lauryl sulfate, stir at 60 r / min for 18 min, cool to 45°C and discharge to obtain a new environmentally friendly water-resistant adhesive for thermal paper labels.
[0025] Example 3; (1) 1 part of tannic acid and 0.5 part of stannous octoate were weighed and mixed at 160°C, stirred at 200 r / min for 20 min, cooled naturally to 25°C, added with 5 parts of 1,4-butenediol, stirred with a magnetic force at 600 r / min for 2 h, filtered to obtain the precipitate, dried naturally in air for 36 h, and dried at 40°C for 48 h with a vacuum degree of -0.096 MPa to obtain 1,4-butenediol containing tannic acid; (2) 2 parts of diphenylmethane diisocyanate and 1 part of 1,4-butenediol were mixed in a molar ratio of 2.0, reacted at 90°C for 90 minutes, cooled to 40°C, added with 2 parts of 1,4-butenediol containing tannin, reacted at 80°C for 16 hours, cooled to 5°C again, and then slowly added with 4 parts of dimethylacetamide under stirring at 2000 r / min to prepare a polyurethane solution; 0.012 times the weight of the polyurethane solution of 4,4'-butylenebis(3-methyl-6-tert-butylphenol) and 0.01 times the weight of the polyurethane solution of 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole were added to the polyurethane solution, stirred at 60 r / min for 20 minutes, and degassed under reduced pressure at room temperature to produce a spinning solution; (3) Dissolve 2 parts of soybean protein in 8 parts of 5% sodium hydroxide aqueous solution at 60°C, react under a 900 MHz microwave for 2 h to obtain a soybean protein pre-liquid, then add 0.1 times the weight of the soybean protein pre-liquid as an initiator hydrogen peroxide to prepare a soybean protein solution; mix 1 part of the soybean protein solution with 5 parts of spinning stock solution, stir at 200 r / min for 6 h to prepare a spinning solution, and dry-spin the spinning solution at a spinning speed of 800 m / min and a hot air temperature of 200°C to prepare a soybean protein polyurethane elastic fiber with a diameter of 1500 nm; (4) 2 parts of corn starch were dispersed in 3 parts of ethyl acetate under the assistance of ultrasound at a power of 80 kHz, 0.2 parts of pyridine were added dropwise, ultrasound was continued for 0.5 h, 0.3 parts of aminoacetyl chloride were added dropwise and stirred at 200 r / min for 1 h, reacted at 25°C for 0.5 h, 10 parts of ethanol were added to terminate the reaction, and the mixture was allowed to stand for 2 h. The ethanol was repeatedly centrifuged and washed 5 times. The solid product after centrifugation was placed in a forced air oven at 80°C and dried for 24 h to obtain esterified starch; 10 parts of esterified starch, 10 parts of polyethylene glycol-400, and 1 part of 1 mol / L sulfuric acid aqueous solution was stirred at 150°C and 100r / min for 12h to obtain an esterified starch modifier; 10 parts of epoxy resin E-51 were mixed with 2 parts of esterified starch modifier, stirred at 100r / min for 1h, placed in an oven at 180°C for 12h, taken out, cooled to 25°C, 1 part of anhydrous ethanol and 1 part of diethylenetriamine were added, stirred at 100r / min for 1h, and vacuumed to 0.096MPa at 10°C to obtain a modified epoxy resin; (5) Heat 45 parts of deionized water to 80°C, slowly add 45 parts of polyvinyl alcohol at a stirring speed of 60 r / min and heat to 95°C. After complete dissolution, cool to 85°C, add 20 parts of butanol and 8 parts of boric acid, stir at 60 r / min for 30 min, then add 24 parts of soybean protein polyurethane elastic fiber, 4 parts of urea, and 26 parts of modified epoxy resin, stir at 60 r / min and heat to 95°C. After reacting for 60 min, lower the temperature to 75°C, add 8 parts of sodium lauryl sulfate, stir at 60 r / min for 20 min, cool to 50°C and discharge to obtain a new environmentally friendly water-resistant adhesive for thermal paper labels.
[0026] Comparative Example 1: The difference between Comparative Example 1 and Example 2 is that step (1) is omitted, and step (2) is changed to: 1.6 parts of diphenylmethane diisocyanate and 1 part of 1,4-butene diol are mixed, reacted at 90° C. for 90 min, cooled to 80° C. for 16 h, cooled to 5° C. again, and then 4 parts of dimethylacetamide are slowly added under stirring at 1500 r / min to prepare a polyurethane solution; 0.012 times the weight of the polyurethane solution of 4,4'-butylenebis(3-methyl-6-tert-butylphenol) and 0.01 times the weight of the polyurethane solution of 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole are added to the polyurethane solution, stirred at 60 r / min for 20 min, and then degassed under reduced pressure at room temperature to form a spinning solution; the remaining steps are the same as those of Example 2.
[0027] Comparative Example 2: The difference between Comparative Example 2 and Example 2 is that step (2) is different, and step (2) (5) is changed to: (2) the spinning solution is dry-spun at a spinning speed of 800 m / min and a hot air temperature of 200° C. to prepare a polyurethane elastic fiber with a diameter of 850 nm; (5) 30 parts of deionized water were heated to 80°C, 30 parts of polyvinyl alcohol were slowly added at a stirring speed of 60 r / min and the temperature was raised to 93°C. After complete dissolution, the mixture was cooled to 80°C, 15 parts of butanol and 7 parts of boric acid were added, and the mixture was stirred at 60 r / min for 30 min. Then, 18 parts of polyurethane elastic fiber, 3 parts of urea and 20 parts of modified epoxy resin were added, the mixture was stirred at 60 r / min and the temperature was raised to 93°C. After reacting for 60 min, the temperature was lowered to 67°C, 8 parts of sodium lauryl sulfate were added, the mixture was stirred at 60 r / min for 18 min, the temperature was lowered to 45°C and the mixture was discharged to obtain a new environmentally friendly water-resistant adhesive for thermal paper labels. The remaining steps were the same as those in Example 2.
[0028] Comparative Example 3: The difference between Comparative Example 3 and Example 2 is that there are no steps (1), (2) and (3), and step (5) is changed to: 30 parts of deionized water are heated to 80°C, 30 parts of polyvinyl alcohol are slowly added at a stirring speed of 60 r / min and the temperature is raised to 93°C. After complete dissolution, the mixture is cooled to 80°C, 15 parts of butanol and 7 parts of boric acid are added, and the mixture is stirred at 60 r / min for 30 min. Then, 12 parts of soy protein, 8 parts of tannic acid, 3 parts of urea and 20 parts of modified epoxy resin are added, the mixture is stirred at 60 r / min and the temperature is raised to 93°C. After reacting for 60 min, the temperature is lowered to 67°C, 8 parts of sodium lauryl sulfate are added, the mixture is stirred at 60 r / min for 18 min, the temperature is lowered to 45°C and the mixture is discharged to obtain a new environmentally friendly water-resistant adhesive for thermal paper labels. The remaining steps are the same as those of Example 2.
[0029] Comparative Example 4: The difference between Comparative Example 4 and Example 2 is that step (4) is different. Step (4) is changed to: 10 parts of corn starch, 10 parts of polyethylene glycol-400, and 1 part of 1 mol / L sulfuric acid aqueous solution are stirred at 150°C and 100 r / min for 12 hours to obtain a starch modifier; 10 parts of epoxy resin E-51 are mixed with 1.5 parts of starch modifier, stirred at 100 r / min for 1 hour, placed in an oven at 180°C for 12 hours, taken out, cooled to 25°C, 1 part of anhydrous ethanol and 1 part of diethylenetriamine are added, stirred at 100 r / min for 1 hour, and evacuated to 0.096 MPa at 5°C to obtain a modified epoxy resin; the remaining steps are the same as those of Example 2.
[0030] Comparative Example 5: The difference between Comparative Example 5 and Example 2 is that there is no step (4), and step (5) is changed to: 30 parts of deionized water are heated to 80°C, 30 parts of polyvinyl alcohol are slowly added at a stirring speed of 60 r / min and the temperature is raised to 93°C. After complete dissolution, the mixture is cooled to 80°C, 15 parts of butanol and 7 parts of boric acid are added, and the mixture is stirred at 60 r / min for 30 min. Then, 18 parts of soybean protein polyurethane elastic fiber, 3 parts of urea, and 20 parts of epoxy resin E-51 are added, the mixture is stirred at 60 r / min and the temperature is raised to 93°C. After reacting for 60 min, the temperature is lowered to 67°C, 8 parts of sodium lauryl sulfate are added, the mixture is stirred at 60 r / min for 18 min, the temperature is lowered to 45°C, and the material is discharged to obtain a new environmentally friendly water-resistant adhesive for thermal paper labels. The remaining steps are the same as those in Example 2.
[0031] Effect example Table 1 below shows the performance analysis results of the new environmentally friendly water-resistant adhesive for thermal paper labels using Examples 1 to 3 of the present invention and Comparative Examples 1 to 5.
[0032]
[0033] From the comparison of the experimental data of water resistance of the embodiment and the comparative example, it can be found that the present invention mixes diphenylmethane diisocyanate and 1,4-butene diol to generate a polyurethane prepolymer with isocyanate as the terminal, and grafts and copolymerizes it with tannic acid to generate a spinning solution to prepare a micron-sized polyurethane elastic fiber; then it is introduced into soybean protein, and the double bonds in the fiber molecular chain polymerize with the amino free radicals of the soybean protein, and multiple phenolic hydroxyl groups are introduced into the molecular structure of the soybean protein, and the synergistic effect with the physical means of microwave radiation changes the aggregation mode between protein molecules, and tannic acid can reduce the colloid interaction between proteins. The effect further destroys the secondary structure of the protein, forms a new dense network structure with the protein to prevent the invasion of water molecules, improves the hydrophobicity of soybean protein, uses aminoacetyl chloride as a reagent to esterify starch, and uses it as a filler additive. Its surface is changed from hydrophilic to hydrophobic due to esterification, thereby improving the water resistance of the adhesive; from the experimental data comparison of the viscosity of the embodiment and the comparative example, it can be found that the surface of the polyurethane elastic fiber grafted with tannic acid in the present invention contains a large number of phenolic hydroxyl groups, which can be used as a hydrogen donor to combine with free radicals, thereby terminating the chain reaction caused by free radicals, and achieving the purpose of anti-oxidation and improving viscosity. The compatibility of the esterified starch with epoxy resin is improved, and it is evenly dispersed. The double bonds on the surface form a cross-linked network structure with the epoxy polar groups, showing an obvious steric hindrance effect. The fiber and soybean protein are added to the epoxy resin, and the starch is attached to the fiber surface to form a chain structure and resin composite, thereby improving the mechanical bonding performance of the adhesive. The polyurethane elastic fibers in the adhesive can also generate hydrogen bonding forces with the plant fibers on the paper, and under the synergistic effect of the protein, the adhesion of the adhesive for thermal paper labels is further improved. From the comparison of the experimental data of biodegradability of the embodiment and the comparative example, it can be found that the present invention, as an environmentally friendly adhesive for notes, uses biological protein, starch, and epoxy resin as raw materials, so that the adhesive can be biodegraded to achieve an environmentally friendly effect.
[0034] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A method for preparing a new environmentally friendly water-resistant adhesive for thermal paper labels, characterized in that: The method comprises the following preparation steps: (1) Weigh 1 part of tannic acid and 0.1-0.5 parts of stannous octoate, mix at 90-160°C, stir at 200 r / min for 20 min, cool naturally to 25°C, add 1-5 parts of 1,4-butenediol, stir magnetically at 500-600 r / min for 2 h, filter and collect the precipitate, air dry naturally, and dry at -0.096 MPa vacuum degree and 30-40°C for 12-48 h to obtain 1,4-butenediol containing tannic acid; (2) 1.2-2 parts of diphenylmethane diisocyanate and 1 part of 1,4-butenediol are mixed, reacted at 90°C for 90 minutes, cooled to 40°C, 1.8-2 parts of 1,4-butenediol containing tannin are added, reacted at 80°C for 16 hours, cooled to 5°C again, and then 4 parts of dimethylacetamide are slowly added under vigorous stirring to prepare a polyurethane solution; 0.012 times the weight of the polyurethane solution of 4,4'-butylenebis(3-methyl-6-tert-butylphenol) and 0.01 times the weight of the polyurethane solution of 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole are added to the polyurethane solution, stirred at 60r / min for 20 minutes, and degassed under reduced pressure at room temperature to produce a spinning solution; (3) dissolving 2 parts of soybean protein in 6-8 parts of sodium hydroxide aqueous solution at a temperature of 40-60° C., reacting under a microwave of 600-900 MHz for 2 h to obtain a soybean protein pre-liquid, and then adding an initiator in an amount of 0.01-0.1 times the weight of the soybean protein pre-liquid to prepare a soybean protein solution; mixing 1 part of the soybean protein solution with 3-5 parts of spinning stock solution, stirring at a speed of 200 r / min for 6 h to prepare a spinning solution, and dry spinning the spinning solution at a spinning speed of 800 m / min and a hot air temperature of 200° C. to prepare a soybean protein polyurethane elastic fiber; (4) Disperse 2 parts of corn starch in 2-3 parts of ethyl acetate under ultrasonic conditions, add 0.2 parts of pyridine dropwise, continue ultrasonication for 0.5 h, add 0.1-0.3 parts of aminoacetyl chloride dropwise and stir at 200 r / min for 1 h, react at 25°C for 0.5 h, add 10 parts of ethanol to terminate the reaction, let stand for 2 h, wash repeatedly with ethanol by centrifugation 4-5 times, and dry the solid product after centrifugation in a forced air oven at 80°C for 24 h to obtain esterified starch; mix 10 parts of esterified starch and 10 parts of poly(vinyl alcohol) Ethylene glycol-400 and 1 part of sulfuric acid solution were stirred at 150°C and 100 r / min for 12 hours to obtain an esterified starch modifier; 10 parts of epoxy resin E-51 were mixed with 1-2 parts of esterified starch modifier, stirred at 100 r / min for 1 hour, placed in an oven at 180°C for 12 hours, taken out, cooled to 25°C, 1 part of anhydrous ethanol and 1 part of diethylenetriamine were added, stirred at 100 r / min for 1 hour, and vacuumed at 0-10°C to obtain a modified epoxy resin; (5) Heat 15-45 parts of deionized water to 80°C, slowly add 15-45 parts of polyvinyl alcohol at a stirring speed of 60 r / min and heat to 90-95°C. After complete dissolution, cool to 75-85°C, add 10-20 parts of butanol and 6-8 parts of boric acid, stir at 60 r / min for 30 min, then add 12-24 parts of soybean protein polyurethane elastic fiber, 2-4 parts of urea, and 13-26 parts of modified epoxy resin, stir at 60 r / min and heat to 90-95°C. After reacting for 60 min, lower the temperature to 60-75°C, add 8 parts of sodium lauryl sulfate, stir at 60 r / min for 15-20 min, cool and discharge the material to obtain a new environmentally friendly water-resistant adhesive for thermal paper labels.
2. The method for preparing a new environmentally friendly water-resistant adhesive for thermal paper labels according to claim 1, characterized in that: The natural air drying time in step (1) is 12-36 hours.
3. The method for preparing a new environmentally friendly water-resistant adhesive for thermal paper labels according to claim 1, characterized in that: The speed of the vigorous stirring in step (2) is 1000-2000 r / min.
4. The method for preparing a novel environmentally friendly water-resistant adhesive for thermal paper labels according to claim 1, characterized in that: The mass fraction of the sodium hydroxide aqueous solution in step (3) is 1-5%.
5. The method for preparing a new environmentally friendly water-resistant adhesive for thermal paper labels according to claim 1, characterized in that: The initiator in step (3) is hydrogen peroxide.
6. The method for preparing a novel environmentally friendly water-resistant adhesive for thermal paper labels according to claim 1, characterized in that: The diameter of the fiber produced in step (3) is 200-1500nm.
7. The method for preparing a novel environmentally friendly water-resistant adhesive for thermal paper labels according to claim 1, characterized in that: The sulfuric acid solution in step (4) is a 1 mol / L sulfuric acid aqueous solution.
8. The method for preparing a new environmentally friendly water-resistant adhesive for thermal paper labels according to claim 1, characterized in that: The ultrasonic condition in step (4) is: the power is 60-80kHz.
9. The method for preparing a novel environmentally friendly water-resistant adhesive for thermal paper labels according to claim 1, characterized in that: In the step (4), the vacuum is drawn to 0.096 MPa.
10. The method for preparing a novel environmentally friendly water-resistant adhesive for thermal paper labels according to claim 1, characterized in that: The discharge temperature in step (5) is 40-50°C.
Citation Information
Cited By
Sulfur autotrophic denitrification filler and preparation method thereof
CN120229820A
Anti-ultraviolet cable and preparation method thereof
CN121260572A